The value of oral health screening for athletes - Gallagher, J.; Fine, P. (Research in Sports Medicine, 2025)
Oral health problems have been reported by athletes to negatively affect their performance, therefore improved oral health has the potential to enhance performance. Reduced performance due to poor oral health is unacceptable and preventable. A rapid literature review was undertaken. Oral diseases such as caries, erosive tooth wear and periodontal diseases do not present with pain in their early stages, and athletes may delay a dental check or even treatment until they perceive a problem. Oral health promotion in sport is most likely to be successful if it is embedded within overall athlete general health and performance promotion. Most members of the athlete support team are not experts in this area and therefore specialist input is needed. Regular checks, provided through oral health screening, are important, not only to identify oral diseases at an early stage but as an opportunity to enhance motivation towards a high standard of oral health.